2007
DOI: 10.1007/s10554-007-9252-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of left ventricular function: comparison of cardiac multidetector-row computed tomography with two-dimension standard echocardiography for assessment of left ventricular function

Abstract: MDCT can be a useful tool to measure LVEF while patients are undergoing CT coronary angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…In addition, ventricular wall motion can be assessed visually by the use of cine loop displays of multiple cardiac phases. According to recent reports [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], measurements for various LV functional parameters with MDCT were correlated and agreed with measurements obtained with MRI, 2D-TTE and ECG-gated single photon emission CT (SPECT). However, the experience with 64-slice MDCT for cardiac function assessment remains limited by small patient numbers and the inclusion of homogeneous patient populations [24][25][26][27][28][29][30][31][32].…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…In addition, ventricular wall motion can be assessed visually by the use of cine loop displays of multiple cardiac phases. According to recent reports [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], measurements for various LV functional parameters with MDCT were correlated and agreed with measurements obtained with MRI, 2D-TTE and ECG-gated single photon emission CT (SPECT). However, the experience with 64-slice MDCT for cardiac function assessment remains limited by small patient numbers and the inclusion of homogeneous patient populations [24][25][26][27][28][29][30][31][32].…”
mentioning
confidence: 67%
“…Multiple studies have been published regarding the assessment of LVEF using 4-, 8-, 16-and 64-slice and dual-source MDCT [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][37][38][39][40][41]. LVEF as determined by the use of MDCT showed good or excellent agreement with the respective measurements from cineventriculography, 2D-echocardiography, MRI and SPECT (Table 3).…”
Section: Lvef With Mdctmentioning
confidence: 95%
“…Recent studies that compared the left ventricular systolic function values obtained by echocardiography and MDCT have demonstrated good correlations (5,14,15). However, left ventricular volume values calculated by MDCT were significantly higher than those obtained by echocardiography.…”
Section: Discussionmentioning
confidence: 98%
“…The accurate and reproducible quantitative assessment of global LV functional parameters requires sufficient temporal resolution, and a number of studies have been conducted to assess LV global function, showing good or excellent agreement with the competitive image modalities using 4-, 8-, 16-and 64-slice MDCT [11,[15][16][17][18][19][20]. However, in those studies patients were administered beta-blockers, and all those studies also revealed a systematic deviation of LV volumes and EF.…”
Section: Discussionmentioning
confidence: 99%